1997
DOI: 10.1007/s004390050518
|View full text |Cite
|
Sign up to set email alerts
|

Distinct spectrum of CFTR gene mutations in congenital absence of vas deferens

Abstract: Congenital absence of the vas deferens (CAVD) is a frequent cause for obstructive azoospermia and accounts for 1%-2% of male infertility. A high incidence of mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene has recently been reported in males with CAVD. We have investigated a cohort of 106 German patients with congenital bilateral or unilateral absence of the vas deferens for mutations in the coding region, flanking intron regions and promotor sequences of the CFTR gene. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
3
20

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(167 citation statements)
references
References 82 publications
11
133
3
20
Order By: Relevance
“…Other groups confirmed the presence of two CFTR mutations in a subset of males with CBAVD (De Braekeleer and Ferec 1996;Wilschanski et al 1996). However, the distribution of CFTR mutations differed between those with CF and those with CBAVD (Dörk et al 1997;Claustres et al 2000). The most frequent is a poly T tract polymorphism located in intron 8 (namely, the IVS8-5T) in the noncoding sequence of the gene, which is an exon 9 splice variant (Chilló n et al 1995).…”
Section: Cftr-related Disordersmentioning
confidence: 90%
“…Other groups confirmed the presence of two CFTR mutations in a subset of males with CBAVD (De Braekeleer and Ferec 1996;Wilschanski et al 1996). However, the distribution of CFTR mutations differed between those with CF and those with CBAVD (Dörk et al 1997;Claustres et al 2000). The most frequent is a poly T tract polymorphism located in intron 8 (namely, the IVS8-5T) in the noncoding sequence of the gene, which is an exon 9 splice variant (Chilló n et al 1995).…”
Section: Cftr-related Disordersmentioning
confidence: 90%
“…Homozygous CBAVD individuals show one severe and one mild pathogenic mutation or two mild mutations, but never two severe mutations. 6 -10 In addition to classic CFTR mutations, up to 40% of CBAVD patients show the 5T allele, that is, five thymidines within intron 8, 7,8,11,12 which results in a reduction of the splicing efficiency of the CFTR gene. 13 This polymorphism is usually found with a 5 -10% prevalence in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of R75Q heterozygosity in the group of unrelated founders (parents) was 0.057 (three in 53), which was slightly higher but statistically not significantly different (P=0.5; Fisher's exact test) from the frequency of 0.011 (four in 94) among healthy German controls. 10 The frequency for R75Q among patients was 0.05 (eight in 138), which was statistically neither different compared to the group of healthy controls (P=0.43) nor to the parents (P=0.64) nor to the healthy siblings (P=0.35). To stratify for non-related patients, we randomly selected one patient from each family.…”
Section: Resultsmentioning
confidence: 76%
“…Instead, R75Q segregated independently from the sarcoidosis phenotype in these families. Previously, we and others reported a relatively high frequency of R75Q among patients with congenital absence of the vas deferens (CAVD), 10,17,18 bronchiectasis, 7,19 atypical mild cystic fibrosis, 20 chronic idiopathic pancreatitis, 21 allergic bronchopulmonary aspergillosis, 22 and sarcoidosis. 7,8 Bombieri et al concluded from their study that R75Q may be a CFTR gene mutation characteristic of sarcoidosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation